Application of LSP texts in translator training - Ilynska, Larisa; Smirnova, Tatjana; Platonova, Marina (Studies in Second Language Learning and Teaching, 2017)
The paper presents discussion of the results of extensive empirical research into efficient methods of educating and training translators of LSP (language for special purposes) texts. The methodology is based on using popular LSP texts in the respective fields as one of the main media for translator training. The aim of the paper is to investigate the efficiency of this methodology in developing thematic, linguistic and cultural competences of the students, following Bloom’s revised taxonomy and European Master in Translation Network (EMT) translator training competences. The methodology has been tested on the students of a professional Master study programme called Technical Translation implemented by the Institute of Applied Linguistics, Riga Technical University, Latvia. The group of students included representatives of different nationalities, translating from English into Latvian, Russian and French. Analysis of popular LSP texts provides an opportunity to structure student background knowledge and expand it to account for linguistic innovation. Application of popular LSP texts instead of purely technical or scientific texts characterised by neutral style and rigid genre conventions provides an opportunity for student translators to develop advanced text processing and decoding skills, to develop awareness of expressive resources of the source and target languages and to develop understanding of socio-pragmatic language use.